Determinants of the Passengers' Light Rail Transit Usage in the Klang Valley Malaysia - Mohd Rizaimy Shaharudin; Amir Imran Zainoddin; Jamaludin Akbar; Dahlan Abdullah; Nur Hannah Saifullah (International Journal of Supply Chain Management, 2018)
The study aims to examine the determinants that motivate passengers to use the Light Rail Transit in The Klang Valley, Malaysia. The factors identified in the study were traffic reduction, advantage of LRT, and attitude. This study used a questionnaire to gather the survey data. The convenience sampling technique was utilised in the study. SmartPLS Version 3 was used to test the hypotheses. The results of the study showed that traffic reduction, advantages of LRT and attitude have a positive influence towards the LRT usage. These significant variables can be used as a guide for the LRT operators to increase the LRT usage. Future research is suggested to include other potential factors that could stimulate more LRT usage and for it to become the preferred mode choice for travelling amongst the users.